2015
DOI: 10.1007/s11914-015-0271-2
|View full text |Cite
|
Sign up to set email alerts
|

The Vestibular System: A Newly Identified Regulator of Bone Homeostasis Acting Through the Sympathetic Nervous System

Abstract: The vestibular system is a small bilateral structure located in the inner ear, known as the organ of balance and spatial orientation. It senses head orientation and motion, as well as body motion in the three dimensions of our environment. It is also involved in non-motor functions such as postural control of blood pressure. These regulations are mediated via anatomical projections from vestibular nuclei to brainstem autonomic centers and are involved in the maintenance of cardiovascular function via sympathet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 131 publications
1
15
0
Order By: Relevance
“…Ideas are emerging on the cerebral benefits of vestibular stimulation which might even spread beyond the brain. For example, recent studies report that the vestibular organ can influence bone and muscle remodeling (Vignaux et al, 2015 ), help synchronize circadian rhythms (Fuller et al, 2002 ; Martin et al, 2015 ), and regulate vegetative and postural blood pressure (Normand et al, 1997 ; Yates et al, 2014 ).…”
Section: Development Of Vestibular Functionsmentioning
confidence: 99%
“…Ideas are emerging on the cerebral benefits of vestibular stimulation which might even spread beyond the brain. For example, recent studies report that the vestibular organ can influence bone and muscle remodeling (Vignaux et al, 2015 ), help synchronize circadian rhythms (Fuller et al, 2002 ; Martin et al, 2015 ), and regulate vegetative and postural blood pressure (Normand et al, 1997 ; Yates et al, 2014 ).…”
Section: Development Of Vestibular Functionsmentioning
confidence: 99%
“…Our understanding of neuronal control has extended from the sympathetic nervous system [14] to the parasympathetic and sensory nervous systems [15,16]. Abnormalities in the central nervous system such as vestibular dysfunction may also indirectly affect bone mass [17]. The role of the central nervous system in bone metabolism and the specific role of adiponectin in skeletal metabolism are addressed in this issue.…”
mentioning
confidence: 99%
“…The vestibular system sends projections to autonomic nervous system centers including brainstem medullary and pontine nuclei (Balaban 1999;Luxon and Pagarkar 2013;Holstein et al 2014). Moreover, the effect of vestibular ablation on bone mineral density seen in rats was abrogated by the concurrent administration of a sympathetic antagonist and in beta receptor knockout mice (Denise et al 2009;Vignaux et al 2013;Vignaux et al 2014;Vignaux et al 2015). Interestingly, the changes in bone mineral density following vestibular lesion in rodents were limited to the weight-bearing lower extremity bones (Levasseur et al 2004;Denise et al 2009;Vignaux et al 2013;Vignaux et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in animals have found that experimentally induced loss of vestibular function leads to decreases in bone mineral density, possibly through effects mediated by the sympathetic nervous system (Levasseur et al 2004;Denise et al 2009;Vignaux et al 2014;Vignaux et al 2015). Although these studies reported no difference in physical activity between control and vestibular-deafferented mice, physical activity level may play an important role as a mediator and/or confounder of the association between vestibular function and BMD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation